ASSESSMENT METHOD OF OPTICAL PROPERTIES OF MATERIALS TO REDUCE OF THE OBJECT-BACKGROUND CONTRAST - J. S. Omer; Y. V. Belyaev; I. M. Tsykman (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Method of determining the spectral reflectance of the polarization properties of materials masking objects from visual observations of the optical channels is proposed and tested. The effectiveness of this method is confirmed by field experiments with speсtral videopolarizing equipment.